PENGARUH PENERAPAN KANTIN SEHAT TERHADAP KARAKTER SISWA DI SDN-SN KURIPAN BANJARMASIN - Tati'ah, Tati'ah (Elementary School Teacher Education of STKIP Al Hikmah Surabaya, 2020)
Abstract                 The purpose of this study was to determine the effect of the application of healthy canteens to the character of students in SDN-SN Kuripan 2 Banjarmasin. The object of this study was the effect of the application of healthy canteens to the character of students in SDN-SN kuripan 2 Banjarmasin, while the subjects in this study were SDN-SN students Excerpt 2 Banjarmasin. The research sample was 10 students in IVC class and 10 students in VA class. The method used is descriptive quantitative, using data digging tools, namely: Questionnaire, and documentation. Data analysis techniques are: Simple Linear Regression, and Conclusions. The conclusions of the study of the influence of the application of healthy canteens to the character of students in SDN-SN excerpts 2 Banjarmasin are as follows: tcount> ttable at a 5% significant level of 3,141> 1,697. Thus there is the effect of the application of healthy canteens to the character of students in the National Standard State School Curriculum 2 Banjarmasin. Based on the results of the study it is recommended that school residents, especially teachers and hawker sellers in the canteen should always provide ethical and moral learning to their students, so that students are expected to have good dedication and health, as well as teach students about the importance of independence from an early age, accustoming students to throw trash in places that have been provided in each of the canteens, responsibility with the school environment includes taking care of cleaning the school canteen.   Abstrak   Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan kantin sehat terhadap karakter siswa di SDN-SN Kuripan 2 Banjarmasin.Objek penelitian ini adalah pengaruh penerapan kantin sehat terhadap karakter siswa di SDN-SN kuripan 2 Banjarmasin, sedangkan subjek dalam penelitian ini adalah siswa SDN-SN Kuripan 2  Banjarmasin. Adapun sampel penelitian adalah siswa kelas IVC yang berjumlah 10 orang dan kelas VA yang berjumlah 30 orang. Metode yang digunakan adalah Deskriptif Kuantitatif, dengan menggunakan alat penggali data yaitu: Angket, dan dokomentasi. Teknik analisis data yaitu : Regresi Linier Sederhana, dan Kesimpulan. Kesimpulan penelitian dari pengaruh penerapan kantin sehat terhadap karakter siswa di SDN-SN kuripan 2 Banjarmasin adalah sebagai berikut: thitung  >  ttabel pada tarap signifikan 5% yaitu 3,141> 1,697. Dengan demikian  ada pengaruh penerapan kantin sehat terhadap karakter siswa di Sekolah Dasar Negeri Standar Nasional Kuripan 2 Banjarmasin. Berdasarkan hasil penelitian maka disarankan kepada warga sekolah khususnya guru dan penjual jajanan di kantin hendaknya selalu memberikan pembelajaran etika dan moral kepada siswa nya, sehingga diharapkan siswa memiliki dedikasi dan kesehatan yang baik, sekaligus mengajarkan siswa tentang pentingnya kemandirian sejak dini, membiasakan siswa membuang sampah pada tempat yang sudah disediakan disetiap masing-masing kantin, tanggung jawab dengan lingkungan sekolahnya termasuk ikut menjaga kebersihan kantin sekolah.